The Effect of Media Mix and Match Puzzle Multiple Number Representation on the Ability to Recognize Number Symbols in Early Childhood - Sapitri, Nur Fitriani; Ilyas, Sitti Nurhidayah; Hajerah; Hasbi (UNIB Press, 2025)
Recognizing number symbols in early childhood is challenging because their abstract nature does not align with the child's concrete thinking stage. Conventional methods, such as flashcards, have proven less effective because they rely solely on memorization. This study aims to test the influence of Media Puzzle Mix and Match Multiple Number Representation on children's ability to recognize number symbols in the 5-6-year age range. This research method uses a quasi-experiment with a pretest-posttest control group design involving 16 children at Al-Ikhsan Kindergarten. The experimental group consisted of 8 children using a puzzle media with six number representations, while the control group consisted of 8 children using conventional flashcards. Results: Data analysis showed a significant increase (p < 0.05) in the experimental group, with an average increase of 22.25% compared with the control group, which was only 5.75%. The conclusion of the Media Puzzle Mix-and-Match Multiple Number Representation is efficacious in improving the ability to recognize number symbols through a multisensory approach aligned with constructivist and dual-coding theories.